2015
DOI: 10.1152/jn.00539.2013
|View full text |Cite
|
Sign up to set email alerts
|

EEG-β/γ spectral power elevation in rat: a translatable biomarker elicited by GABAAα2/3-positive allosteric modulators at nonsedating anxiolytic doses

Abstract: Benzodiazepine drugs, through interaction with GABA(Aα1), GABA(Aα2,3), and GABA(Aα5) subunits, modulate cortical network oscillations, as reflected by a complex signature in the EEG power spectrum. Recent drug discovery efforts have developed GABA(Aα2,3)-subunit-selective partial modulators in an effort to dissociate the side effect liabilities from the efficacy imparted by benzodiazepines. Here, we evaluated rat EEG and behavioral end points during dosing of nine chemically distinct compounds that we confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 38 publications
6
46
0
Order By: Relevance
“…Based on these in vitro data, TP003 was postulated to be an α3-selective modulator and had clear anxiolytic-like effects in rats and squirrel monkeys (Dias et al, 2005). However, two recent studies failed to replicate the findings of the initial report by Dias et al (2005) regarding the subtype selectivity of TP003, and instead demonstrated comparable efficacies at all diazepam-sensitive α-subunits (Christian et al, 2015;de Lucas et al, 2015). Moreover, the presumably α3-selective compound SB-205384 (4-amino-7-hydroxy-2-methyl-5,6,7,8,-tetrahydrobenzo[b]thieno [2,3-b]pyridine-3-carboxylic acid, but-2-ynyl ester), which was shown to have anxiolytic-like actions (Navarro et al, 2006), was later found to be a positive modulator at α5-and α6-GABA A Rs in addition to α3-GABA A Rs (Heidelberg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these in vitro data, TP003 was postulated to be an α3-selective modulator and had clear anxiolytic-like effects in rats and squirrel monkeys (Dias et al, 2005). However, two recent studies failed to replicate the findings of the initial report by Dias et al (2005) regarding the subtype selectivity of TP003, and instead demonstrated comparable efficacies at all diazepam-sensitive α-subunits (Christian et al, 2015;de Lucas et al, 2015). Moreover, the presumably α3-selective compound SB-205384 (4-amino-7-hydroxy-2-methyl-5,6,7,8,-tetrahydrobenzo[b]thieno [2,3-b]pyridine-3-carboxylic acid, but-2-ynyl ester), which was shown to have anxiolytic-like actions (Navarro et al, 2006), was later found to be a positive modulator at α5-and α6-GABA A Rs in addition to α3-GABA A Rs (Heidelberg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In an apparent contrast, the compound TP003 (4,2′-difluoro-5′-[8-fluoro-7-(1-hydroxy-1-methylethyl)imidazo[1,2-a′]pyridin-3-yl]biphenyl-2-carbonitrile), reported to be selective for α3-GABA A Rs in in vitro assays on recombinant receptors, was found to have anxiolytic-like effects in several species (Dias et al, 2005), which led to the widely accepted conclusion that α3-GABA A Rs may also mediate anxiolytic effects of benzodiazepines (eg, Korpi et al, 2015;Sigel and Steinmann, 2012). However, two recent studies were unable to reproduce the α3-selectivity of TP003 in recombinant receptors (Christian et al, 2015;de Lucas et al, 2015), raising the question whether the anxiolytic-like action of TP003 is really dependent on modulation of α3-GABA A Rs, and, on a broader scale, whether α3-GABA A Rs are involved at all in the modulation of anxietyrelated behaviors. Furthermore, a conditional deletion of the α5-subunit in PKCδ+ neurons in the central amygdala resulted in increased anxiety in the open-field (OF) and elevated plus maze (EPM) tests (Botta et al, 2015), suggesting a role for α5-GABA A Rs in anxiety regulation.…”
Section: Introductionmentioning
confidence: 99%
“…But there is also evidence from earlier experiments, that beta1 waves are under the control of GABA [20]. However, it is generally accepted, that spectral beta power is related to GABAergic transmission [21].…”
Section: Discussionmentioning
confidence: 98%
“…Pharmacological intervention with the serotonergic system resulted in changes of alpha1 frequencies [25], whereas dopaminergic activity could be recognized by changes of alpha2 waves [26]. Finally, changes in the glutamatergic transmitter system were reflected in changes of beta1 activity [11] and GABA-ergic modulation was recognized by changes in beta2 frequencies [27]. Table 7.…”
Section: Discussionmentioning
confidence: 99%